Court-appointed expert consultation in Italy: an ethnographic study of parents’ beliefs, expectations, and experiences - Iudici, Antonio; Rainieri, Francesca; Fiorini, Tania (Frontiers in Psychology, 2025)
This study focuses on the process of Court-Appointed Expert Consultation (Consulenza Tecnica d’Ufficio, CTU) that parents involved in high-conflict separations must undergo. The CTU is an expert psychological assessment commissioned by the court to assist legal proceedings, aimed at providing judges with essential information for well-founded decisions. Given that this is a relatively new but rapidly growing field in Italy, also considering the increasing divorce rates, specific scientific literature on the subject is still limited. Therefore, the purpose of this research is to examine in greater depth how separated parents perceive and experience this process, considering the psychological aspects involved, their expectations, their evaluation of the investigation’s utility, and the motivations underlying their request. Through qualitative research based on semi-structured interviews, the results highlight that participants view the CTU as a useful decision-making tool for the judge, but also as a mediator and guardian of minors. However, parents often confuse the role of the CTU with that of a mediator. Many parents expect a “corrective” CTU for the other parent, based on the idea that the problem lies with the other party. Indeed, while the request primarily arises to protect the children, it is also aimed at countering the other parent. Parents described the process as a demanding but ultimately useful, offering opportunities for reflection and new insights. The CTU is ultimately seen as a “validation” of parental suitability and a tool for vindication, but also as not always resolving family conflicts. We believe these findings can be highly useful for the Courts that initiate the investigation, as well as for all professionals involved, including psychologists, lawyers, and juvenile judges.